Health and wellness @ Uni: a module to enhance students' health and well-being / Salmi Razali - Razali, Salmi (UiTM Press, 2023)
This module guidebook aims to empower students of Universiti Teknologi MARA with knowledge of how to be healthy. It is a valuable resource and provides guidance on a comprehensive way of managing mental health problems among UiTM's students. It is hoped that students use this module guidebook to ensure they have optimum mental health and to assist them in managing their psychological problems.